2011
DOI: 10.1007/s11655-011-0897-6
|View full text |Cite
|
Sign up to set email alerts
|

Protection of ultra-filtration extract from Danggui Buxue Decoction (当归补血汤) on oxidative damage in cardiomyocytes of neonatal rats and its mechanism

Abstract: The EDBD has protection on cardiomyocytes injured by H(2)O(2) through improving cell antioxidant ability, up-regulating hsp70 expression, and inhibiting caspase-3 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…Ligusticum Chuanxiong prevents serum deprivation-induced PC12 cell apoptosis [32]. The extract from Danggui Buxue decoction, a subsidiary formula of BYHWD, protected the cardiomyocytes from H 2 O 2 -induced apoptosis through downregulation of caspase-3 expression [33]. Thus, the effects of these active anti-apoptotic components of BYHWD played an important role in preventing the ventricular remodeling through down regulation of AI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligusticum Chuanxiong prevents serum deprivation-induced PC12 cell apoptosis [32]. The extract from Danggui Buxue decoction, a subsidiary formula of BYHWD, protected the cardiomyocytes from H 2 O 2 -induced apoptosis through downregulation of caspase-3 expression [33]. Thus, the effects of these active anti-apoptotic components of BYHWD played an important role in preventing the ventricular remodeling through down regulation of AI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that both Radix Angelicae Sinensis [31] and TPG [30] activated Bcl-2 and inhibited Bax expression both at gene and protein level, then the Bcl-2/Bax ratio was increased as a matter of course. In addition, extract from Danggui Buxue decoction [33] downregulated caspase-3 in the cardiomyocytes of the rat's heart. There was a decrease of Bax expression and caspase 3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts of AS are also commonly incorporated into dietary health supplements. According to recent studies, AS appears to possess anti‐cancer and anti‐oxidant activities . Despite our knowledge of these effects, the exact mechanism by which AS produces these pharmacological effects is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular formulation is Danggui Buxue Tang (DBT) composed of Astragalus and Angelica at a 5 : 1 ratio, which is mainly used to treat anemia due to various causes via promoting hematopoiesis. 1) In recent years, studies have shown that DBT also has other pharmacological effects, such as enhancing immunity, 2) antagonizing diabetic nephropathy, 3) cardiovascular protection, 4) anti-fibrosis, 5,6) estrogen-like effect, 7,8) among others. Concerning the hematopoietic function of the AstragalusAngelica combination, most studies have revealed that Astragalus mixed with Angelica at 5 : 1 can strongly promote hematopoiesis.…”
mentioning
confidence: 99%